The influence of methodological trends of accounting research for the period (1926 - 2019) in the formulation and construction of accounting theory: Analytical exploratory study - Maher Ali Hussain Shamam; Ahmed Mohammed Khalel (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Accounting researches during the period (1926 - 2019) contributed to the development of accounting through the study، analysis and discussion of many emerging topics in accounting، whether the subjects related to the intellectual philosophical side، or what related to the application side related to accounting practices and procedures that applied by professional accountants. Based on its analysis، discussion and construction of its assumptions and proof it on one of the two prevailing approaches in accounting which are: (Normative approach) having deductive roots، and (Positive approach) having inductive roots. The research problem come out in the query about the effect resulting from the change in the accounting research methodology during the period (1926–2019) from its reliance on the standard procedure and its transition to the postural approach on the formulation and construction of accounting theory، and the effect of this transition on the possibility of reaching to the acceptable and comprehensive accounting theory، and that was done through analyzing the methodological trends of accounting research published in the most important journals representing the accounting community in the world (TAR، CAR، JAR، AOS)، and then analyzing the reasons for this transition or change and its impact on the possibility of getting an acceptable and comprehensive accounting theory by building a basic assumption for the research which is: The shift in the direction of accounting research approaches from the normative approach (as a prevailing approach) During the period (1926-1968) to the positive approach (as a prevailing approach) during the period (1968 - 2019) have a negative effect on the attempts to formulate and construct the acceptable and comprehensive accountancy theory، which is an assumptions that its validity was proved (based on the results of the analysis of the questions contained in the questionnaire form prepared for this research)، where the researchers reached a number of conclusions، whereas the most important one is that this transition led to creating a number of partial and superficial accounting theories، in addition to the dissolution of accounting as an independent knowledge field in the vessels of science and other knowledge fields، which led to the inability to develop the theory of accounting or reaching to the acceptable and comprehensive accounting theory.